Neisseria gonorrhoeae Aggregation Reduces Its Ceftriaxone Susceptibility - Liang-Chun Wang; Madeline Litwin; Zahraossadat Sahiholnasab; Wenxia Song; Daniel C. Stein (MDPI AG, 2018)
Antibiotic resistance in Neisseria gonorrhoeae (GC) has become an emerging threat worldwide and heightens the need for monitoring treatment failures. N. gonorrhoeae, a gram-negative bacterium responsible for gonorrhea, infects humans exclusively and can form aggregates during infection. While minimal inhibitory concentration (MIC) tests are often used for determining antibiotic resistance development and treatment, the knowledge of the true MIC in individual patients and how it relates to this laboratory measure is not known. We examined the effect of aggregation on GC antibiotic susceptibility and the relationship between bacterial aggregate size and their antibiotic susceptibility. Aggregated GC have a higher survival rate when treated with ceftriaxone than non-aggregated GC, with bacteria in the core of the aggregates surviving the treatment. GC lacking opacity-associated protein or pili, or expressing a truncated lipooligosaccharide, three surface molecules that mediate GC-GC interactions, reduce both aggregation and ceftriaxone survival. This study demonstrates that the aggregation of N. gonorrhoeae can reduce the susceptibility to antibiotics, and suggests that antibiotic utilization can select for GC surface molecules that promote aggregation which in turn drive pathogen evolution. Inhibiting aggregation may be a potential way of increasing the efficacy of ceftriaxone treatment, consequently reducing treatment failure.